QCD factorization for the four-body leptonic B-meson decays - Wang, Chao; Wang, Yu-Ming; Wei, Yan-Bing (The journal of high energy physics, 2022)
A bstract Employing the QCD factorization formalism we compute B u − → γ ∗ ℓ v ¯ ℓ form factors with an off-shell photon state possessing the virtuality of order m b Λ QCD and m b 2 , respectively, at next-to-leading order in QCD. Perturbative resummation for the enhanced logarithms of m b /Λ QCD in the resulting factorization formulae is subsequently accomplished at next-to-leading logarithmic accuracy with the renormalization-group technique in momentum space. In particular, we derive the soft-collinear factorization formulae for a variety of the subleading power corrections to the exclusive radiative B u − → γ ∗ W ∗ form factors with a hard-collinear photon at O α s 0 . We further construct a complete set of the angular observables governing the full differential distribution of the four-body leptonic decays B u − → ℓ ′ ℓ ¯ ′ ℓ v ¯ ℓ with ℓ , ℓ′ ∈ { e , μ } and then perform an exploratory phenomenological analysis for a number of decay observables accessible at the LHCb and Belle II experiments, with an emphasis on the systematic uncertainties arising from the shape parameters of the leading-twist B -meson light-cone distribution amplitude in heavy quark effective theory.